1981
DOI: 10.1111/j.1399-0039.1981.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculoid leprosy and HLA in Japanese

Abstract: HLA phenotypes of 54 patients with tuberculoid leprosy were compared with those of 167 healthy controls. Frequencies of HLA-A, -B and -C antigens did not differ significantly between the leprosy patients and the controls. However, an increase in the frequencies of DR1, DR2, DRW8 and MT1 antigens and a decrease in the frequencies of DR4 and MT3 antigens were observed in the leprosy patients. Statistical evidence was presented that MT1 antigens were primarily associated with tuberculoid leprosy in Japanese patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…38,39 Increased HLA-DR2 frequencies have been reported in both tuberculoid and lepromatous patients compared to controls. 15,18,19,28,29,31,40,41 Association studies have also shown that DR2 is increased in leprosy patients of all subtypes compared to controls. 42,43 Family-based studies have shown a skewed distribution of DR2 alleles in Indian 44 and Egyptian tuberculoid siblings.…”
Section: Class II Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Increased HLA-DR2 frequencies have been reported in both tuberculoid and lepromatous patients compared to controls. 15,18,19,28,29,31,40,41 Association studies have also shown that DR2 is increased in leprosy patients of all subtypes compared to controls. 42,43 Family-based studies have shown a skewed distribution of DR2 alleles in Indian 44 and Egyptian tuberculoid siblings.…”
Section: Class II Regionmentioning
confidence: 99%
“…DQ alleles, especially DQw1 have been shown to be associated with tuberculoid leprosy in India, 26,27 Korea, 19 Thailand 28 and Japan, 29 and with lepromatous leprosy in India 15 and Japan. 18,30 DQw1 was also implicated in a meta-analysis of pooled association studies 31 and in a Venezuelan lepromatous family study 10 whereas in Shaw's recent Brazilian family study significant evidence for linkage and association to tuberculoid leprosy and possibly leprosy per se was found with DQB1, DQA1 and DRB1 variants.…”
Section: Class II Regionmentioning
confidence: 99%
“…they may represent an unusual response to different antigens in different individuals, whereas the chronicity of Wegener's granulomatosis and its association with DR2 may reflect a more fundamental abnormality in the host's immune response. The frequency of HLA-B7 and/or B7.DR2 is increased in subsets of other chronic granulomatous diseases such as sarcoidosis and leprosy (24)(25)(26). In addition, a single patient with lymphomatoid granulomatosis was also found to have HLA-DR2 (unpublished observation).…”
Section: Discussionmentioning
confidence: 90%
“…Although, in general, HLA studies have not supported predominance of one or more HLA factors in unclassified schizophrenia (McGuffin et al 1983), in all six centers where a paranoid subgroup was delineated, HLA A9 was increased; HLA Al was significantly increased in hebephreruc patients compared with controls in three of four centers (McGuffin et al 1981). Miyanaga et al (1984) also reported elevated incidence of DRW8 in a group of Japanese patients with schizophrenia.…”
Section: Genetic Factorsmentioning
confidence: 98%